The Challenge of Precise Measurement of Precision - John Watson; Jay Rodgers (International Society of Explosives Engineers, 1998)
The world of blasting and explosive use continues to evolve into one which relies heavily on measurement, quantification, process control, and information feedback as a means of contributing to operational improvements. More than ever good blast performance, once thought to be a result of someone’s “artistic ability”, is giving way to “hard science” and measurement techniques. Variability in product performance and process control is becoming less tolerable with increasing environmental issues, regulatory pressure and public awareness.